Uji Potensi Antikanker Ekstrak Tiga Spesies Tanaman Sansevieria Dengan Metode Brine Shrimp Lethality Test (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2021)
Indonesia has the potential for abundant natural resources including medicinal plants that have anticancer activity. The aim of this study is to determine the anticancer potential of three Sansevieria plant species extracts using the Brine Shrimp Lethality Test Method. This research is an experimental research method by invitro. Anticancer potency test using the BSLT method on extracts of three species of Â lidah mertua leaves consisting of Sansevieria trifasciata, Sansevieria tiger green, and Sansevieria Zeylanica. The results showed that the three species of Sansevieria have potential as anticancer, but the most potential as an anticancer is Sansevieria tiger Hijau because it is very toxic with an LC50 value of 29.646 ppm.Â